Aerospace sensors - Nebylov, A. V. (Aleksandr Vladimirovich) (Sensors technology series, 2013)
Modern air and space craft demand a huge variety of sensing elements for detecting and controlling their behavior and operation. These sensors often differ significantly from those designed for applications in automobile, ship, railway, and other forms of transportation, and those used in industrial, chemical, medical, and other areas. This book offers insight into an appropriate selection of these sensors and describes their principles of operation, design, and achievable performance along with particulars of their construction. Drawn from the activities of the International Federation of Automatic Control (IFAC), especially its Aerospace Technical Committee, the book provides details on the majority of sensors for aircraft and many for spacecraft, satellites, and space probes. It is written by an international team of twelve authors representing four countries from Eastern and Western Europe and North America, all with considerable experience in aerospace sensor and systems design. Highlights include: * coverage of aerospace vehicle classification, specific design criteria, and the requirements of onboard systems and sensors; * reviews of airborne flight parameter sensors, weather sensors and collision avoidance devices; * discussions on the important role of inertial navigation systems (INS) and separate gyroscopic sensors for aerospace vehicle navigation and motion control; * descriptions of engine parameter information collection systems, including fuel quantity and consumption sensors, pressure pick-ups, tachometers, vibration control, and temperature sensors; and * descriptions and examples of sensor integration.